ADDRESSING CHALLENGES TO BUILDING INFORMATION MODELLING IMPLEMENTATION IN UK: DESIGNERS' PERSPECTIVES - Abdul-Majeed MAHAMADU; Dharshana NAVENDREN; Patrick MANU; Rotimi JOSEPH; Krzysztof DZIEKONSKI (Journal of Construction Project Management and Innovation)
Building information modelling (BIM) has been proposed as a technology-enabled process for more efficient and effective management of information in digital and virtual environments. Many challenges, however, exist and undermine its effective implementation within the construction industry. The identification of these challenges is critical to the successful implementation and adoption of BIM, especially in view of many implementation risks. Despite the critical role of the design phase to project delivery and BIM usage, few studies have sought to interrogate the challenges faced by designers and the solutions that are being applied to address them. To address this gap, this study aimed to identify and classify challenges faced by designers with particular focus on proposed solutions for alleviating the identified challenges. Through a qualitative research strategy, semi-structured interviews were used to solicit perspectives of UK design professionals on design profession-specific BIM implementation challenges and solutions. Findings reveal that challenges are mostly organisational and external environmental issues with rather cursory allusion to technological challenges which are widely reported in the literature. The solutions identified for alleviating designers’ BIM implementation challenges include earlier input and integration from whole supply chain as well as more support institutional support and facilitation. The promotion of open-BIM standards, tailored insurance as well as principal supplier leadership were also proposed as viable solutions to BIM implementation challenges. Variations in the challenges and proposed solutions appear to differ across different categories of firms investigated in this study, particularly in relation to the cost of implementation.